Próba oceny polityki spożycia. Na przykładzie gospodarki rybnej w Polsce - Szulce, Halina (Wydział Prawa i Administracji UAM, 1967)
Generally speaking the policy of fish consumption is a very complicated matter. In the postwar period fish consumption in Poland has been determined by the size of supplies. We have had a situation where an effective demand could not be met. The structure of fish consumption — in comparison with the interwar period — has also changed considerably. This was due to the changes in frontiers, the widening of the fishing areas entry into entirely new areas and finally the changes in the consumption habits of some groups of population. In Poland it is taken for granted that fish consumption has a substitutional and not a complementary character. This seems to be confirmed by a high indice of income elasticity for fish and processed fish. There exist great discrepancies between fish consumption in different regions of the country and in the urban — rural aspect. The fish consumption fluctuated — exluding the factor of a buying power of the population — according not only to the size of supplies but also according to various economic and outer-economic solutions linked with the market sphere. Besides the organization of distribution, material and technical basis of turnover, different links of said turnover, instutional structure — a very important role played the price polices. The present price policy restraints to a large degree the substitution between meat and fish foodstuffs. Fish foodstuffs are not at present a durable substitution for meat, because of uneven supplies (from the territorial as well as seasonal apects). It should be stressed that the development of substitution between meat and fish is of great importance to the policies aiming at market stabilisation.
An attempt to asses the policy of consumption. Based on fish economy in Poland